Pertanian Beras Organik di Kecamatan Susukan, Banjarnegara - , RAHADIYAN ADIANTO, Drs. Hadriyanus Suharyanto M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Today, the need is not just the quantity of food consumed but the quality of the food itself. Organic farming to be an absolute requirement to produce a higher quality food than inorganic farming. Minimize and even not using synthetic chemicals in agriculture is able to produce a healthy crop is consumed and also other sustainable positive impact. Unfortunately not all farmers, rice in particular, want to switch to organic farming. This is found in the rice farmers in the district Susukan and will be revealed in this study the reasons why farmers do not want rice farming organically. In this study using qualitative methods as it is based on the formulation of explanatory question \\"why\\". Reasons or because individuals who do not want to do something that can be caused by many factors and so are the rice farmers Susukan district. Rice farmers respondent drawn at random. Agricultural Extension Centres Susukan district also interviewed to see the form of organic agricultural extension are routed. It adds organic rice farmers who individually and independently develop organic agriculture. Results reported observation that fertility paddy rice farming conditions are very poor due to the use of agricultural chemicals in excessive inorganic. In addition, there is still minimal number of farmers to develop organic farming. Results of interviews on rice farmers mentioned that the reason they are reluctant to organic farming is the lack of science and technology owned. While counseling is done BPP Susukan district also is less effective in mengedukas farmers themselves. Appropriate advice to implement organic farming, particularly in sub- Susukan rice is introducing the basics of organic farming itself. Rice farmers in the district are now familiar with organic farming Susukan Adala use of fertilizers and organic pesticides manufacturing production while the real essence of organic farming is the use of natural resources and local knowledge is available and affordable by the farmers themselves so that farmers are able to cultivate and provide material support agriculture. It is shown that one of the farmers go organic preformance is long term. Pak Bambang Supriya, native farmers Susukan district has been able to recognize and process all the natural resources and local knowledge that is available for use in the surrounding organic farming. He is not dependent on anyone in running his farm because a lot of sources that can be utilized. Had other farmers and the government is willing and able to apply what Mr. Bambang Supriyadi is that organic farming can be run effectively and efficiently.